กลยุทธ์การเพิ่มยอดขายวัสดุก่อสร้างของร้าน 3B Material อำเภอเมือง จังหวัดกาฬสินธุ์: Marketing Strategies to Increase Construction Material Sales For 3B Material Store in Amphoe Muang, Kalasin Province - ยงประพัฒน์ พงศ์พิช (Journal of Applied Economics and Management Strategy, 2018)
การศึกษานี้ มีวัตถุประสงค์เพื่อศึกษาถึงพฤติกรรมและปัจจัยที่มีผลต่อการตัดสินใจซื้อวัสดุก่อสร้างของผู้บริโภค เพื่อกำหนดกลยุทธ์ ในการเพิ่มยอดขายวัสดุก่อสร้างของร้าน 3B Material ให้ได้ตามเป้าหมายที่กำหนด โดยหาสาเหตุของยอดขายที่ลดลงด้วยการการวิเคราะห์สภาพแวดล้อมทั่วไป สภาพแวดล้อมทางการแข่งขันของธุรกิจวัสดุก่อสร้าง การวิเคราะห์จุดแข็ง จุดอ่อน โอกาส และอุปสรรคของธุรกิจ และปัจจัยเชิงกลยุทธ์ เมื่อทราบถึงสาเหตุ และปัจจัยต่างๆ จึงได้นำข้อมูลดังกล่าวมากำหนดกลยุทธ์ทางการตลาด ประกอบด้วย แผนกลยุทธ์ระยะสั้น 5 กลยุทธ์คือ กลยุทธ์ใจดีมีเครดิต กลยุทธ์จ่ายสดลดเลย กลยุทธ์ซื้อ 3B มีทองใส่ กลยุทธ์ 1 เดือน 1 โปรโมชั่น และกลยุทธ์โฉมใหม่ ไฉไลกว่าเดิม ในส่วนแผนกลยุทธ์ยาวมีวัตถุประสงค์เพื่อรักษาฐานลูกค้าเดิม และขยายฐานลูกค้าใหม่ เพื่อสร้างความจงรักภักดีต่อแผนกลยุทธ์ และเกิดการซื้อซ้ำ และเพื่อเพิ่มศักยภาพการพัฒนาการให้บริการของร้าน 3B Material คือ กลยุทธ์แม่เหล็กดึงดูดใจ เป็นการพัฒนาคุณภาพสินค้า และบริการ โดยคาดหวังว่ากลยุทธ์ดังกล่าวจะทำให้ร้าน 3B Materialมียอดขายที่เพิ่มขึ้นอย่างน้อยร้อยละ 10 จากยอดขาย 7,482,520.84 บาท ในปี2557 เพิ่มขึ้นเป็น 8,230,772.92 บาท ในปี2558 ภายในระยะเวลา 3 เดือน ตั้งแต่เดือนตุลาคม ถึงเดือนธันวาคม 2558 This study aims to investigate the marketing strategies to increase construction material sales for 3B Material store in Amphoe Muang, Kalasin province. The methodology was conducted by studying and analyzing the general information of people who have done the questionnaires and factors which affect purchase decision making of construction materials as well as examining the causes of decreased turnover through an analysis of general and competition surroundings of construction materials business, strength and weakness, trade barrier, and strategic factors. After knowing causes and factors related to the business, this study analyzed data to define marketing strategies including short-term strategy and long-term strategy. Short-term strategy composes of five strategies such as creditworthy strategy, “pay cash gain discount” strategy, “purchase 3B get gold” strategy, “one month one promotion” strategy, and new strategy. Long-term strategy aims to keep regular customers and extend new costumers base in order to strengthen the loyalty of strategy and reordering. It also aims to increase potentiality of service development in 3B Material. Long-term strategy is the attractive strategy, which is the development of product and service quality. These strategies are expected to increase the 3B Material turnover 10 percent from 7,482,520.84 baht in 2014 to 8,230,772.92 baht in 2015 within 3 months from October to December 2015.